Polymerizable composition, liquid crystal cured film, preparation method of liquid crystal cured film and display device
By using a polymerizable composition containing compounds of formulas I, II, and III, a liquid crystal curable film is formed by light irradiation polymerization, which solves the problems of low productivity and high cost in the prior art, and realizes the preparation of a highly efficient and low-cost vertically aligned liquid crystal curable film suitable for display devices.
Patent Information
- Application Number
- CN202311140174.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-05
AI Technical Summary
Existing technologies require multiple coating processes when manufacturing vertically aligned liquid crystal curing films, resulting in low productivity and high costs. Furthermore, the interaction between conventional vertically aligned films and liquid crystal curing films affects black state transmittance. There is a desire to provide an effective vertically aligned liquid crystal curing film without using PI.
A polymerizable composition containing one or more compounds of formula I, II and III is used to polymerize a liquid crystal curable film by light irradiation, avoiding the use of PI-oriented films, improving production efficiency and reducing costs.
A vertically oriented liquid crystal curing film was obtained without using PI, which improved production efficiency, reduced production costs, and the resulting liquid crystal curing film has a large Rth adjustment range and low haze, resulting in good display performance of display devices.
Smart Images

Figure BDA0004435271830000011 
Figure BDA0004435271830000021 
Figure BDA0004435271830000041
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical films, and more specifically to a polymerizable composition, a liquid crystal cured film containing the composition, a preparation method thereof, and an application of the same in a display device. Background Art
[0002] The elliptically polarizing plate is an optical component formed by stacking a polarizing plate and a phase difference plate. For example, in an organic EL image display device and other devices that display images in a planar state, it is used to prevent light reflection at the electrodes constituting the device. As the phase difference film layer constituting the elliptically polarizing plate, the so-called λ / 4 wave plate is usually used. A single-layer λ / 4 wave plate can only achieve the effect of black state display at a straight viewing angle, and light leakage will still occur at an oblique viewing angle. By further assembling a vertically oriented liquid crystal curing film into the elliptically polarizing plate with a horizontally oriented liquid crystal curing film, the oblique hue change during black state display when the elliptically polarizing plate is used in an organic EL display device can be suppressed.
[0003] In the past, in order to manufacture a vertically oriented liquid crystal cured film, a vertically oriented film for aligning a polymerizable liquid crystal compound in a vertical direction was usually required. In order to obtain a coating film from an oriented film forming composition and a liquid crystal cured film forming composition, at least two or more coating film forming steps were required, which resulted in a problem of reduced productivity. Moreover, for a conventional vertically oriented film, a polyimide (PI) layer was required to induce the homeotropic orientation required by the liquid crystal layer. In addition to a significant increase in cost, the interaction between PI and the vertically oriented liquid crystal cured film often resulted in a negative impact on the black state transmittance. Therefore, it is hoped that the required uniform vertical orientation can be provided without using PI.
[0004] Therefore, in order to improve production efficiency and reduce production costs, how to provide a liquid crystal curing film that can provide the required vertical alignment without using PI is an urgent problem to be solved in the field of optical film technology. Summary of the invention
[0005] In order to solve one or more of the technical defects mentioned above, the present invention provides a polymerizable composition. By using the polymerizable composition, a vertically oriented liquid crystal curing film can be obtained without using a PI orientation film, which can effectively improve production efficiency and save production costs. The vertically oriented liquid crystal curing film has a large Rth adjustment range and very low haze.
[0006] In order to achieve the above-mentioned beneficial technical effects, the present invention provides a polymerizable composition, comprising one or more compounds of formula I and one or more compounds of formula II, and further comprising one or more compounds of formula III as additives;
[0007]
[0008]
[0009] In Formula I, L1 represents H, F, Cl, CN or a linear, branched or cyclic alkyl group having 1 to 25 carbon atoms, an alkenyl group having 2 to 25 carbon atoms, or an alkynyl group having 2 to 25 carbon atoms, wherein one or more non-adjacent -CH2- groups are optionally substituted by -O-, -S-, -CO-, -CO-O-, -O-CO-, -O-CO-O-, or -N-, and the -O- or -S- atoms in the substituted groups are not directly connected to each other, and wherein one or more H atoms in one or more -CH2- groups are each optionally substituted by halogen;
[0010] represents 1,4-cyclohexylene, 1,4-phenylene, 2,6-naphthylene, 1,5-naphthylene or 1,4-naphthylene;
[0011] Sp1 and Sp2 each independently represent a spacer; P1 and P2 each independently represent a polymerizable group or H, and at least one of P1 and P2 represents a polymerizable group; a, b, and c each independently represent 1, 2, or 3;
[0012] In formula II, S 11 I represents a polymerizable group; 11 represents a spacer or a single bond; H 11 represents an alkyl group, an alkoxy group, a thioalkyl group, an alkylcarbonyl group, an alkoxycarbonyl group, an alkylcarbonyloxy group or an alkoxycarbonyloxy group having 1 to 10 carbon atoms; M 11 is F, Cl, CN, NO2, OCN, SCN, a fluoroalkyl group having 1 to 10 carbon atoms, or a fluoroalkoxy group having 1 to 10 carbon atoms;
[0013] In formula III, X1 and X3 each independently represent H, F, Cl, CN, OCN, CHO, COOH, NO2; X2 represents a single bond, -CH=CH-, -C≡C- or a cyclic group; m, n, q each independently represent an integer of 0-10;
[0014] The mass percentage content of the compound represented by formula I in the polymerizable composition is 30% to 70%, the mass percentage content of the compound represented by formula II is 40% to 70%; the added amount of the compound represented by formula III relative to the mass of the polymerizable composition is 0.5% to 2.5%.
[0015] A second object of the present invention is to provide a liquid crystal cured film, which is obtained by polymerizing the aforementioned polymerizable composition.
[0016] The third object of the present invention is to provide a method for preparing a liquid crystal cured film, which is the method for preparing the aforementioned liquid crystal cured film.
[0017] A fourth object of the present invention is to provide a display device comprising the aforementioned polymerizable composition or the aforementioned liquid crystal cured film.
[0018] Effects of the Invention
[0019] The present invention provides a polymerizable composition. By using the polymerizable composition, a vertically oriented liquid crystal curing film can be obtained without using a PI orientation film, which can effectively improve production efficiency and save production costs. The vertically oriented liquid crystal curing film formed by the polymerizable composition has a large Rth adjustment range and very low haze. The preparation method of the liquid crystal curing film provided by the present invention is simple and easy to implement, effectively improves production efficiency, saves production costs, and can achieve large-scale production. The display device provided by the present invention, comprising a liquid crystal curing film formed by the above-mentioned polymerizable composition, has a good display effect. DETAILED DESCRIPTION
[0020] The "auxiliary agents" mentioned in the present invention are components for improving the stability of the polymerizable composition of the present invention, including antioxidants, photoinitiators, leveling agents, surfactants, chain transfer agents, sensitizers, UV inhibitors, polymerization inhibitors, etc. These additives can be selectively added in one or more or none of them according to the stability performance of the formula.
[0021] Antioxidant: In order to improve the stability of the polymerizable composition of the present invention, it is preferable to add an antioxidant. Examples of such compounds include hydroquinone derivatives, nitrosoamine-based polymerization inhibitors, hindered phenol-based antioxidants, and more specifically, tert-butyl hydroquinone, methyl hydroquinone, "Q-1300" and "Q-1301" manufactured by Wako Pure Chemical Industries, Ltd., and "IRGANOX 1010", "IRGANOX 1035", "IRGANOX 1076", "IRGANOX 1098", "IRGANOX 1135", "IRGANOX 1330", "IRGANOX 1425", "IRGANOX 1520", "IRGANOX 1726", "IRGANOX 245", "IRGANOX 259", "IRGANOX 3114", "IRGANOX 3790", "IRGANOX 5057", and "IRGANOX 565" manufactured by BASF.
[0022] The photoinitiator refers to a photopolymerization initiator, and preferably contains at least one kind. Specifically, examples thereof include "Irgacure 651", "Irgacure 184", "Darocur 1173", "Irgacure 907", "Irgacure 127", "Irgacure 369", "Irgacure 379", "Irgacure 819", "Irgacure 2959", "Irgacure 1800", "Irgacure 250", "Irgacure 754", "Irgacure 784", "Irgacure OXE01", "Irgacure OXE02", "Lucirin TPO", "Darocur 1173", "Darocur MBF" and the like manufactured by BASF Japan Ltd.
[0023] Leveling agent: The polymerizable composition of the present invention may contain at least one surfactant in order to reduce uneven film thickness. Examples of the surfactant that may be contained include alkyl carboxylates, alkyl phosphates, alkyl sulfonates, fluoroalkyl carboxylates, fluoroalkyl phosphates, fluoroalkyl sulfonates, polyoxyethylene derivatives, fluoroalkyl ethylene oxide derivatives, polyethylene glycol derivatives, alkyl ammonium salts, fluoroalkyl ammonium salts, etc., and fluorinated surfactants are particularly preferred. Specifically, "Megafac F-251", "Megafac F-444", "Megafac F-477", "Megafac F-510", "Megafac F-552", "Megafac F-553", "Megafac F-554", "Megafac F-555", "Megafac F-556", "Megafac F-557", "Megafac F-558", "Megafac F-559", "Megafac F-560", "MegafacF-561", "Megafac F-562", "Megafac F-563", "MegafacF-565", "Megafac F-567", "Megafac F-568", "Megafac F-569", "Megafac F-570", "Megafac F-571", "MegafacR-40", "Megafac "Megafac RS-41", "Megafac R-43", "Megafac R-94", "Megafac RS-72-K", "Megafac RS-75", "Megafac RS-76-E", and "Megafac RS-90" are manufactured by DIC Corporation.
[0024] Chain transfer agent: The polymerizable composition of the present invention preferably contains a chain transfer agent in order to improve adhesion to a substrate. The chain transfer agent is preferably a thiol compound, more preferably a monothiol, dithiol, trithiol, or tetrathiol compound.
[0025] Polymerization inhibitor: Examples include phenolic compounds, quinone compounds, amine compounds, thioether compounds, and nitroso compounds.
[0026] The term "coating" as used herein refers to a coating method for obtaining the polymerizable composition of the present invention, and can be performed by a known and commonly used method such as an applicator method, a rod coating method, a spin coating method, a roll coating method, a direct gravure coating method, a reverse gravure coating method, a flexo coating method, an inkjet method, a die coating method, a cap coating method, a dip coating method, a slit coating method, etc. After the polymerizable composition is coated, it is dried as necessary.
[0027] The "polymerization" mentioned in the present invention refers to the polymerization operation of the polymerizable composition of the present invention. When the polymerization is carried out by light irradiation, it is preferably irradiated with ultraviolet light of 390 nm or less, and most preferably irradiated with light of 250 to 370 nm in wavelength.
[0028] The "Re" mentioned in the present invention refers to the film internal retardation, that is, the horizontal retardation, which is the retardation parallel to the film surface of the phase difference film.
[0029] The "Rth" mentioned in the present invention refers to the vertical retardation, that is, the retardation perpendicular to the surface of the phase difference film.
[0030] The "room temperature" mentioned in the present invention refers to the temperature range of 15°C to 35°C.
[0031] The "spacer" mentioned in the present invention represents an alkyl group having 1-10 carbon atoms, an alkyl group having 1-10 carbon atoms substituted with fluorine, an alkoxy group having 1-10 carbon atoms, an alkoxy group having 1-10 carbon atoms substituted with fluorine, an alkenyl group having 2-10 carbon atoms, an alkenyl group having 2-10 carbon atoms substituted with fluorine, an alkenyloxy group having 3-8 carbon atoms or an alkenyloxy group having 3-8 carbon atoms substituted with fluorine, an alkynyl group having 2-10 carbon atoms, an alkynyl group having 2-10 carbon atoms substituted with fluorine, an alkynyloxy group having 2-8 carbon atoms or an alkynyloxy group having 3-8 carbon atoms substituted with fluorine, and any one or more unconnected -CH2- in the group represented by the spacer may be independently and optionally substituted with -O-, -S-, -COO-, or -OOC-;
[0032] The "polymerizable group" mentioned in the present invention means a methacrylate group, an acrylate group, a vinyl group or an oxirane group, and an acrylate group or a methacrylate group is more preferable.
[0033] [Polymerizable composition]
[0034] The present invention provides a polymerizable composition, comprising one or more compounds of formula I and one or more compounds of formula II, and further comprising one or more compounds of formula III as additives;
[0035]
[0036] In Formula I, L1 represents H, F, Cl, CN or a linear, branched or cyclic alkyl group having 1 to 25 carbon atoms, an alkenyl group having 2 to 25 carbon atoms, or an alkynyl group having 2 to 25 carbon atoms, wherein one or more non-adjacent -CH2- groups are optionally substituted by -O-, -S-, -CO-, -CO-O-, -O-CO-, -O-CO-O-, or -N-, and the -O- or -S- atoms in the substituted groups are not directly connected to each other, and wherein one or more H atoms in one or more -CH2- groups are each optionally substituted by halogen;
[0037] represents 1,4-cyclohexylene, 1,4-phenylene, 2,6-naphthylene, 1,5-naphthylene or 1,4-naphthylene;
[0038] Sp1 and Sp2 each independently represent a spacer; P1 and P2 each independently represent a polymerizable group or H, and at least one of P1 and P2 represents a polymerizable group; a, b, and c each independently represent 1, 2, or 3;
[0039] In formula II, S 11 I represents a polymerizable group; 11 represents a spacer or a single bond; H 11 represents an alkyl group, an alkoxy group, a thioalkyl group, an alkylcarbonyl group, an alkoxycarbonyl group, an alkylcarbonyloxy group or an alkoxycarbonyloxy group having 1 to 10 carbon atoms; M 11 is F, Cl, CN, NO2, OCN, SCN, a fluoroalkyl group having 1 to 10 carbon atoms, or a fluoroalkoxy group having 1 to 10 carbon atoms;
[0040] In formula III, X1 and X3 each independently represent H, F, Cl, CN, OCN, CHO, COOH, NO2; X2 represents a single bond, -CH=CH-, -C≡C- or a cyclic group; m, n, q each independently represent an integer of 0-10;
[0041] The mass percentage content of the compound represented by formula I in the polymerizable composition is 30% to 70%, the mass percentage content of the compound represented by formula II is 40% to 70%; the added amount of the compound represented by formula III relative to the mass of the polymerizable composition is 0.5% to 2.5%.
[0042] The polymerizable composition of the present invention is preferably, in Formula II, M 11 Indicates CN.
[0043] In the polymerizable composition of the present invention, preferably, in formula III, X1 represents CHO, X3 represents H, and the cyclic group represented by X2 is a cycloalkyl group having 3 to 8 carbon atoms or an aryl group having 6 to 15 carbon atoms.
[0044] The polymerizable composition of the present invention preferably further comprises one or more auxiliary agents, wherein the auxiliary agent comprises an antioxidant, a photoinitiator, a leveling agent, a surfactant, a chain transfer agent, a sensitizer, an anti-ultraviolet agent or an inhibitor.
[0045] Preferably, the compound represented by the aforementioned formula I is selected from the group consisting of compounds represented by formulas I1-I20,
[0046]
[0047]
[0048]
[0049] wherein t and u each independently represent 1, 2, 3, 4, 5, 6, 7 or 8. Based on the solubility and compatibility of the above compounds, as well as safety standards, compounds represented by Formula I4-8, Formula I10-12, Formula I14-15, and Formula I18-20 are preferred.
[0050] More preferably, the compound represented by the above formula I is selected from the group consisting of compounds represented by the following formula I4-1 to formula I20-3,
[0051]
[0052]
[0053]
[0054]
[0055]
[0056] More preferably, the compound represented by the above formula I is selected from the compounds represented by formula I4-3, formula I6-2, formula I6-3, formula I7-2, formula I7-3, formula I11-2, formula I11-3, formula I14-2, formula I14-3, formula I18-2, formula I18-3, and formula I20-1.
[0057] Preferably, the compound represented by the aforementioned formula II is selected from the group consisting of compounds represented by formula II1-II5,
[0058]
[0059] Preferably, the compound represented by the aforementioned formula III is selected from the group consisting of compounds represented by formula III1-III5,
[0060]
[0061]
[0062] [Liquid crystal cured film]
[0063] The second object of the present invention is to provide a liquid crystal cured film obtained by polymerizing the aforementioned polymerizable composition.
[0064] Preferably, the aforementioned liquid crystal cured film is a vertically aligned liquid crystal cured film.
[0065] Preferably, the Rth of the liquid crystal cured film is between 50 nm and 500 nm.
[0066] Preferably, the liquid crystal cured film has a thickness of 1 μm to 5 μm.
[0067] [Method for preparing liquid crystal cured film]
[0068] The third object of the present invention is to provide a method for preparing a liquid crystal cured film, which is as follows:
[0069] The first step is to dissolve the above polymerizable composition into a solvent to form a polymerizable composition solution;
[0070] The second step is to apply the polymerizable composition solution onto the corona-treated substrate film to form a polymerizable composition solution layer;
[0071] The third step is to place the substrate film on which the polymerizable composition solution layer is formed on a hot stage for heating;
[0072] The fourth step is to irradiate the heated substrate film with ultraviolet light to form a liquid crystal cured film.
[0073] Preferably, the coating is performed using a wire bar coater.
[0074] Preferably, the aforementioned solvent is a mixed solvent of butanone and toluene in a weight ratio of 1:2.
[0075] Preferably, the heating temperature of the hot stage is 90° C. and the heating time is 90 seconds.
[0076] Preferably, the ultraviolet irradiation is carried out at 80°C, using 365nm ultraviolet irradiation, with a cumulative light intensity of ≥500mJ / cm 2 .
[0077] [Display Devices]
[0078] A fourth object of the present invention is to provide a display device comprising the aforementioned polymerizable composition or the aforementioned liquid crystal cured film.
[0079] Example
[0080] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0081] In the present invention, the preparation methods are conventional methods unless otherwise specified, the raw materials used are available from public commercial channels unless otherwise specified, the temperature is in degrees Celsius (°C), and the specific meanings of other symbols and test conditions are as follows:
[0082] The thickness of the obtained vertically aligned liquid crystal cured film was measured using an ellipsometer, and the testing equipment was M220 manufactured by JASCO Corporation.
[0083] The delay amount of the liquid crystal cured film was measured by bonding it to glass with 25μm OCA optical adhesive manufactured by SDK, and then peeling the vertically oriented liquid crystal of the stack of vertically oriented liquid crystal cured films obtained above from the base film; for the obtained stack comprising glass, OCA optical adhesive, and vertically oriented liquid crystal cured film, the horizontal phase difference and vertical phase difference of the vertically oriented liquid crystal cured film were measured using the Optipro equipment of Shin-Etsu Chemical Co., Ltd. of Japan.
[0084] The evaluation method of the surface state is to measure the haze of the optically anisotropic layer using a haze meter ("Haze-Gard II" manufactured by Toyo Seiki Seisaku-sho) for the laminate containing glass, OCA optical glue, and vertically oriented liquid crystal cured film obtained above. As a result of the measurement, if the haze is less than 0.5%, the surface state is judged to be "good", if the haze is 0.5%-1%, the surface state is judged to be "slightly turbid", and if it is above 1%, the surface state is judged to be "turbid". In addition, the surface state of the optically anisotropic layer is visually observed under a fluorescent lamp. If the shrinkage wrinkles of the film and the haze are not observed, it is judged to be "good", and if they are observed, it is judged to be "poor".
[0085] As a preferred embodiment, the compounds represented by Formula I, Formula II, and Formula III are preferably the compounds represented by the following formulae:
[0086]
[0087] The leveling agent is preferably Megafac F-556 manufactured by DIC Corporation; the photoinitiator is preferably Irgacure 369 manufactured by BASF Corporation; and the antioxidant is preferably Irganox 1076 manufactured by BASF Corporation.
[0088] The present invention is described below using the following specific embodiments:
[0089] Example
[0090] Example 1
[0091] The polymerizable composition solution and the liquid crystal cured film were prepared according to the composition and mass parts in Table 1 below.
[0092] The method for preparing the polymerizable composition solution is as follows:
[0093] Formula I19-3 and Formula II1 were mixed at a mass ratio of 40:60 to obtain a mixture. To 100 parts by mass of the obtained mixture, 1.5 parts by mass of Formula III1, 0.5 parts by mass of leveling agent Megafac F-556, 4 parts by mass of photoinitiator Irgacure369, and 0.7 parts by mass of antioxidant IRGANOX1076 were added, and a mixed solvent of methyl ethyl ketone and toluene (weight ratio of methyl ethyl ketone: toluene = 1:2) was further added as a solvent to make the solid content 25% by weight, and heated to 40°C to dissolve for 1 hour. The obtained mixture was filtered using a membrane filter with a pore size of 0.45 μm to obtain a polymerizable composition solution.
[0094] The preparation method of the liquid crystal cured film is as follows:
[0095] In the first step, a polymerizable composition solution is obtained according to the above preparation method.
[0096] In the second step, the polymerizable composition solution is coated on the corona-treated substrate film to form a polymerizable composition solution layer.
[0097] The substrate film used was PET film (CH-195Y) manufactured by Nanya Co., Ltd. The corona treatment was performed using a Hefeng corona treatment machine with a cleaning speed of 50 mm / s. The purpose of the corona treatment was to generate alcohol or ketone functional groups on the surface of the substrate. A wire bar coater was used for coating.
[0098] In the third step, the substrate film with the polymerizable composition solution layer formed thereon is placed on a hot plate for heating at a temperature of 90° C. for 90 seconds.
[0099] In the fourth step, the heated substrate film is irradiated with ultraviolet light at 80° C. to form a liquid crystal cured film.
[0100] The ultraviolet irradiation is performed using a high pressure mercury lamp (Unicure VB-15201BY-A, manufactured by Ushio Electric Co., Ltd.) to irradiate the polymerizable composition solution layer with ultraviolet rays. The accumulated light intensity at a wavelength of 365 nm in a nitrogen atmosphere is ≥500 mJ / cm2.
[0101] The thickness of the liquid crystal cured film provided in Example 1 is 1.2 μm.
[0102] Table 1 Composition and weight of polymerizable composition of Example 1
[0103] Ⅰ20-1 Ⅱ1 Ⅲ1 Megafac F-556 Irgacure369 Antioxidants 40 60 1.5 0.5 4 0.7
[0104] Embodiments 2 to 5
[0105] The same polymerizable composition solution and liquid crystal cured film preparation method as in Example 1 were used to prepare polymerizable composition solutions and liquid crystal cured films according to Tables 2 to 5 below. The thicknesses of the liquid crystal cured films provided in Examples 2 to 5 were 1.1 μm, 1.1 μm, 1.3 μm, and 1.1 μm, respectively.
[0106] Table 2 Composition and weight of polymerizable composition of Example 2
[0107] Ⅰ20-1 Ⅱ1 Ⅲ1 Megafac F-556 Irgacure369 Antioxidants 30 70 1.5 0.5 4 0.7
[0108] Table 3 Composition and weight of polymerizable composition of Example 3
[0109] Ⅰ20-1 Ⅱ1 Ⅲ1 Megafac F-556 Irgacure369 Antioxidants 50 50 1.5 0.5 4 0.7
[0110] Table 4 Composition and weight of polymerizable composition of Example 4
[0111] Ⅰ20-1 Ⅱ1 Ⅲ1 Megafac F-556 Irgacure369 Antioxidants 40 60 0.5 0.5 4 0.7
[0112] Table 5 Composition and weight of polymerizable composition of Example 5
[0113] Ⅰ20-1 Ⅱ1 Ⅲ1 Megafac F-556 Irgacure369 Antioxidants 40 60 2.5 0.5 4 0.7
[0114] Embodiments 6 to 8
[0115] Using the same polymerizable composition solution and liquid crystal cured film preparation method as in Example 1, using the polymerizable composition composition shown in Table 1, liquid crystal cured films with thicknesses of 2.1 μm, 2.9 μm, and 4.7 μm were prepared as Examples 6 to 8.
[0116] Comparative Examples 1 to 3
[0117] The same polymerizable composition solution and liquid crystal cured film preparation method as in Example 1 were used to prepare polymerizable composition solutions and liquid crystal cured films according to Tables 6 to 8 below. The liquid crystal cured films provided in Comparative Examples 1 to 3 had thicknesses of 1.2 μm, 1.1 μm, and 1.2 μm, respectively.
[0118] Table 6 Comparative Example 1 Composition and weight of polymerizable composition
[0119] Ⅰ20-1 Ⅲ1 Megafac F-556 Irgacure369 Antioxidants 100 1.5 0.5 4 0.7
[0120] Table 7 Comparative Example 2 Composition and mass fraction of polymerizable composition
[0121] Ⅰ20-1 Ⅱ1 Ⅲ1 Megafac F-556 Irgacure369 Antioxidants 70 30 1.5 0.5 4 0.7
[0122] Table 8 Comparative Example 3 Composition and mass fraction of polymerizable composition
[0123] Ⅰ20-1 Ⅱ1 Megafac F-556 Irgacure369 Antioxidants 50 50 0.5 4 0.7
[0124] Comparative Example 4
[0125] The polymerizable composition solution and the liquid crystal cured film were prepared according to Table 4 above, except that the coating was performed by spin coating and glass was used as the substrate film, and the other steps of the preparation method of the liquid crystal cured film remained the same as those of Example 4. The thickness of the liquid crystal cured film provided in Comparative Example 4 was 1.5 μm.
[0126] Comparative Examples 5 to 7
[0127] Comparative Examples 5 to 7 all prepared polymerizable composition solutions and liquid crystal cured films according to Table 1 above. The difference is that the liquid crystal cured film provided in Comparative Example 5 was irradiated with ultraviolet light at room temperature, the PET substrate film used in the liquid crystal cured film provided in Comparative Example 6 was not corona treated, and the liquid crystal cured film provided in Comparative Example 7 was irradiated with ultraviolet light at 40°C.
[0128] Table 9 below shows the evaluation results of the tests on the liquid crystal cured films provided in the embodiments and comparative examples.
[0129] Table 9 Evaluation results of the liquid crystal cured films of the examples and comparative examples
[0130]
[0131] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A polymerizable composition, characterized in that Contains one or more compounds of formula I and one or more compounds of formula II, and further contains one or more compounds of formula III as additives; In Formula I, L1 represents H, F, Cl, CN or a linear, branched or cyclic alkyl group having 1 to 25 carbon atoms, an alkenyl group having 2 to 25 carbon atoms, or an alkynyl group having 2 to 25 carbon atoms, wherein one or more non-adjacent -CH2- groups are optionally substituted by -O-, -S-, -CO-, -CO-O-, -O-CO-, -O-CO-O-, or -N-, and the -O- or -S- atoms in the substituted groups are not directly connected to each other, wherein one or more H atoms in one or more -CH2- groups are each optionally substituted by halogen; represents 1,4-cyclohexylene, 1,4-phenylene, 2,6-naphthylene, 1,5-naphthylene or 1,4-naphthylene; Sp1 and Sp2 each independently represent a spacer group; P1 and P2 each independently represent a polymerizable group or H, and at least one of P1 and P2 represents a polymerizable group; a, b, c each independently represent 1, 2 or 3; In formula II, S 11 represents a polymerizable group; I 11 represents a spacer group or a single bond; H 11 represents an alkyl group, alkoxy group, thioalkyl group, alkylcarbonyl group, alkoxycarbonyl group, alkylcarbonyloxy group or alkoxycarbonyloxy group having 1 to 10 carbon atoms; M 11 represents F, Cl, CN, NO2, OCN, SCN, a fluoroalkyl group having 1 to 10 carbon atoms, or a fluoroalkoxy group having 1 to 10 carbon atoms; In formula III, X1 and X3 each independently represent H, F, Cl, CN, OCN, CHO, COOH or NO2; X2 represents a single bond, -CH=CH-, -C≡C- or a cyclic group; m, n, and q each independently represent an integer from 0 to 10; The mass percentage content of the compound represented by formula I in the polymerizable composition is 30% to 70%, the mass percentage content of the compound represented by formula II is 40% to 70%; the added amount of the compound represented by formula III relative to the mass of the polymerizable composition is 0.5% to 2.5%.
2. The polymerizable composition according to claim 1, characterized in that In the formula II, M 11 Indicates CN.
3. The polymerizable composition according to claim 1, characterized in that In the formula III, X1 represents CHO, X3 represents H, and X2 represents a cycloalkyl group having 3 to 8 carbon atoms or an aryl group having 6 to 15 carbon atoms.
4. The polymerizable composition according to claim 1, characterized in that The invention also contains one or more auxiliary agents, which include antioxidants, photoinitiators, leveling agents, surfactants, chain transfer agents, sensitizers, anti-ultraviolet agents or polymerization inhibitors.
5. A liquid crystal cured film, characterized in that: The liquid crystal cured film is formed by polymerizing the polymerizable composition according to any one of claims 1 to 4.
6. The liquid crystal cured film according to claim 5, characterized in that: The liquid crystal cured film is a vertically aligned liquid crystal cured film.
7. The liquid crystal cured film according to claim 5, characterized in that: The Rth of the liquid crystal cured film is between 50 nm and 500 nm.
8. The liquid crystal cured film according to claim 5, characterized in that: The liquid crystal cured film has a thickness of 1 μm to 5 μm.
9. A method for preparing a liquid crystal cured film, characterized in that: include: The first step is to dissolve the polymerizable composition according to any one of claims 1 to 4 into a solvent to form a polymerizable composition solution; The second step is to apply the polymerizable composition solution onto the corona-treated substrate film to form a polymerizable composition solution layer; The third step is to place the substrate film on which the polymerizable composition solution layer is formed on a hot stage for heating; The fourth step is to irradiate the heated substrate film with ultraviolet light to form a liquid crystal cured film.
10. A display device, characterized in that: The invention comprises the polymerizable composition according to any one of claims 1 to 4 or the liquid crystal cured film according to any one of claims 5 to 8.
Citation Information
Patent Citations
Polymerizable composition and film using same
CN106471023A
Photoalignable positive c-plate retarder
CN114144708A
Polymerizable liquid crystal compound, polymerizable liquid crystal composition, phase difference film, elliptical polarizing plate, and organic EL display device
CN115315645A
alpha-FLUOROACRYLATE COMPOUND AND COMPOSITION, AND POLYMER THEREOF
JP2005112850A
Optically anisotropic body
WO2018151070A1